Functional properties and characterization of yogurt fortified with Synsepalum dulcificum (Schumach. & Thonn.) Daniell and microencapsulated Lactococcus lactis Gh1 - Fazilah, Nurul Farhana (2019)
Nowadays, functional food market is dominated by dairy based probiotic products mainly yogurt. The nutritional values of yogurt can be further enhanced by the inclusion of Synsepalum dulcificum (Schumach. & Thonn.) Daniell extract and the addition of locally isolated probiotic Lactococcus lactis Gh1. S. dulcificum is a plant that possesses unique characteristics that can be used as a healthy food additive which acts as taste modifier besides providing antioxidant and anti-diabetic effects. The screening results of seed, leaf and pulp of S. dulcificum showed that pulp extracts contained significantly (P<0.05) higher antioxidant (85.69 ± 0.004) and phenolic content (15.93 ± 0.002 µg GAE Equiv. / g sample) than the other plant parts. More interestingly, S. dulcificum pulp also has stronger anti-diabetic properties than the standard drug, acarbose and hence it was chosen to be incorporated into yogurt. L. lactis Gh1 was encapsulated via extrusion (with alginate-starch coating agent) and spray drying (with gum Arabic and S.dulcificum pulp) methods to increase the cells viability. A total of seven different yogurts (C.plain (plain yogurt), C.pulp (contained pulp extract), F.plain (contained free cell L. lactis Gh1), F.pulp (contained free cell L. lactis Gh1 and pulp extract), B.plain (contained alginate-starch encapsulated L. lactis Gh1), B.pulp (contained pulp extract and alginate-starch encapsulated L. lactis Gh1), S.dry (contained spray dried L. lactis Gh1 coated with gum Arabic and pulp) were formulated. The yogurts were fermented at 42°C until pH 4.5 prior to storage at 4°C for 21 days. All the yogurts fortified with pulp extract showed a faster rate of pH reduction (~3 hours) than the plain yogurt (6 hours). The total phenolic content (TPC) of all yogurts showed an increasing trend throughout the storage. The presence of S. dulcificum pulp extract elevated (P<0.05) the TPC in the yogurts whereas the antioxidant activity (DPPH assay) and inhibitory activity towards the key enzymes associated with diabetes (α-amylase and α-glucosidase) showed a gradual increase on the first 7 days but decreased afterward. In comparison, yogurts fortified with pulp extract showed a higher (P<0.05) antioxidant and anti-diabetic activity than the plain yogurt. The viability of L. lactis Gh1 in yogurt showed the highest survivability even on the last day (day 21) of refrigerated storage when it was being encapsulated in beads and according to the following order: B.plain (9.43 log CFU/mL)>B.pulp (9.04 log CFU/mL)> F.pulp (8.26 log CFU/mL) > S.dry (8.08 log CFU/mL)> F.plain (6.76 log CFU/mL). Meanwhile, the CFU/mL of the yogurt starter cultures, Streptococcus thermophilus and Lactobacillus dulbrueckii of all yogurts were drastically increased for the first week of storage especially for yogurts added with a non- microencapsulated L. lactis Gh1 (F.plain and F.pulp) but started to decrease after day 7. The flow behaviour of all yogurt samples had exhibited shear thinning behaviour with n<1. In general, the incorporation of S. dulcificum and microencapsulated L. lactis Gh1 had greatly enhanced the quality and potential benefits of the functional yogurt products.